Review paperHigh-dose-rate pre-operative endorectal brachytherapy for patients with rectal cancer - Vuong, Té; Devic, Slobodan (Journal of Contemporary Brachytherapy, 2015)
High-dose-rate endorectal brachytherapy (HDREBT) is an image guided brachytherapy treatment for patients with rectal cancer. It is based on tumor imaging with magnetic resonance in particular, which is used to choose eligible patients and improve tumor visualization. Treatment planning is performed using 3D CT simulation and treatment planning. The treatment is given on an outpatient basis and requires minimal local anesthesia. The validation of the technique was carried out through a preoperative study and is now explored as part of a radical treatment for early rectal cancer or as a boost modality. We describe technical aspects of the HDREBT and we discuss the ongoing institutional review board approved studies exploring the clinical applications of this treatment modality for patients with rectal cancer: 1) as a neoadjuvant treatment for patients with operable rectal tumor; 2) as a option to improve local control in patients with newly diagnosed rectal cancer but with previous pelvic radiation.